Pooled analysis of central venous pressure and brain natriuretic peptide levels in patients with extubation failure - Cao, Jianghong; Wang, Beibei; Zhu, Lili; Song, Lu (Pain medicine, 2022)
Background: extubation failure is related to prolonged hospital stay, high mortality and care cost. In recent years, cardiovascular insufficiency has been considered as a common cause of failed extubation, and some studies have shown that central venous pressure (CVP) and brain natriuretic peptide (BNP) can predict the extubation outcome. Therefore, we conducted a pooled analysis to evaluate that the CVP and BNP levels in critically ill patients subjected to mechanical ventilation are predictors of extubation failure. Methods: Three online electronic databases such as web of science, EMBASE, and Cochrane Library are systematically searched up to October 2021. All data are analyzed using Review Manager 5.4. The pooled analysis results were performed depending on standardized mean differences (SMD) with 95 % confidence intervals (CI) of the CVP and BNP levels for each study. Results: A total of 13 studies with 47 561 participants were included in our study. Our results showed that elevated CVP levels were significantly associated with the risk of failed extubation (SMD: 0.54, 95 % CI: 0.07 to 1.02, P = 0.03). This association also appeared after extubation (SMD: 1.39, 95 % CI: 0.37 to 2.40, P = 0.008), but it did not appear before extubation (SMD: 0.04, 95 % CI: -0.50 to 0.59, P = 0.88). Similarly, Our results also showed that increased BNP levels is closely related to extubation failure (SMD: 0.72, 95 % CI: 0.48 to 0.96, P < 0.00001). This relationship also occurs before (SMD: 0.60, 95 % CI: 0.29 to 0.90, P = 0.0001) and after (SMD: 0.92, 95 % CI: 0.54 to 1.30, P < 0.00001) extubation. Conclusions: This study showed that elevated CVP and BNP levels are associated with risk of extubation failure in critically ill patients. Compared with CVP level, BNP level is a more sensitive and accurate predictor of extubation failure.